2017
DOI: 10.3390/molecules22030396
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasonic-Assisted Enzymatic Extraction Conditions for Improving Total Phenolic Content, Antioxidant and Antitumor Activities In Vitro from Trapa quadrispinosa Roxb. Residues

Abstract: Stems are the important residues of Trapa quadrispinosa Roxb., which are abundant in phenolic compounds. Ultrasonic-assisted enzymatic extraction (UAEE) is confirmed as a novel extraction technology with main advantages of enhancing extraction yield and physiological activities of the extracts from various plants. In this study, UAEE was applied to obtain the highest yield of phenolic content, strongest antioxidant, and antitumor activities and to optimize the extraction conditions using response surface metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 50 publications
5
20
0
Order By: Relevance
“…Basically, extraction is the first step in the isolation process to obtain bioactive compounds from biomass materials with its purpose to maximize the content of target compounds for their further utilization. To obtain flavonoids from plant materials, several methods have been applied to enhance extraction efficiency [15,16]. Studies have shown that not only the extraction yield but also the extraction technique is affected by the extracting solvent [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basically, extraction is the first step in the isolation process to obtain bioactive compounds from biomass materials with its purpose to maximize the content of target compounds for their further utilization. To obtain flavonoids from plant materials, several methods have been applied to enhance extraction efficiency [15,16]. Studies have shown that not only the extraction yield but also the extraction technique is affected by the extracting solvent [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…ose methods are timeconsuming, have low extraction efficiency, and result in the loss of bioactivities of the flavonoids due to high extraction temperature [19]. To address these problems, microwaveassisted extraction [15] and supercritical fluid extraction [20] have been developed for the extraction of flavonoids [15]. Although those methods efficiently extract flavonoids from plant materials, the microwave-assisted extraction is difficult to scale up and requires high microwave power, which increases energy consumption [15,21], whereas the supercritical method proceeds at high pressure (48 MPa), which requires expensive reactor and rises a safety concern [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and stirring speed can affect extraction time [13,18,19,22]. Temperature dramatically influences solubility of solutes, diffusion coefficients and dielectric water constants [15,19,23]. So the KAI technique determines the stirring rate and the extraction time be included in the optimization variable.…”
Section: Resultsmentioning
confidence: 99%
“…The standard used for the determination of TPC is gallic acid [15][16][17]. Determination of TPC uses the folin-ciocalteu reagent with the formation of a stable blue color as an important indicator in the reaction.…”
Section: Total Phenolic Content (Tpc) Assaymentioning
confidence: 99%